PELATIHAN ASESSMENT ONLINE BERBASIS GAME EDUCATIF MELALUI APLIKASI QUIZIZZ DI SMPN 3 MERAUKE - Nova Lina Sari Habeahan; Novike Bela Sumanik (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2023)
The Covid-19 pandemic has forced teachers to have skills in using various applications to support the learning process. This service aims to improve teachers' pedagogic competence and digital literacy in educational game-based online assessments through the quizizz application at SMPN 3 Merauke. This service is focused on making interactive quizzes and how to assess using the quizizz application. This service will be carried out on October 28, 2021 at SMPN 3 Merauke. The number of participants who attended were 20 people. The methods used in this service are lectures, discussions and demonstrations. The results obtained in this service are training using the Quizizz learning media can help teachers improve pedagogic competence. So that learning in the classroom is more fun and makes students' learning motivation increase because it is covered with games. What is no less important is being able to help teachers in terms of assessment because grades automatically appear so that both teachers and students get benefits and benefits. This service also increases the digital literacy of teachers at SMPN 3 Merauke because they can deftly create questions using Quizizz media